1989
DOI: 10.1093/jmedent/26.2.91
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cocaine in Tissues on the Development Rate of Boettcherisca peregrina (Diptera: Sarcophagidae)

Abstract: Larvae of the flesh fly, Boettcherisca peregrina (Robineau-Desvoidy), were reared on the tissue of rabbits to study the effects of cocaine and benzoylecognine on development rates. The rabbits were given 35, 69, and 137 mg of cocaine through cardiac puncture. From hours 30 to 70, larvae developed more rapidly on tissue containing cocaine, benzoylecognine, or both, from rabbits injected with 69 and 137 mg of cocaine than on tissue from rabbits injected with 35 mg of cocaine or no cocaine. Total development time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
62
1
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(68 citation statements)
references
References 0 publications
3
62
1
2
Order By: Relevance
“…the toxicologist's point of view). According to the literature, drugs already detected in larvae include barbiturates (phenobarbital [1], secobarbital [2], amylobarbital and barbital [3]), benzodiazepines (diazepam [4], temazepam [5]), antidepressants (amitriptyline [5,6,7,8,9], nortriptyline [7], trimipramine [5]), opiates/opioids (morphine+codeine [10,11,12,13,14,15,16], propoxyphene [6]), amphetamine derivatives (amphetamine [3], MDMA +MDA [17]), cocaine and/or benzoylecgonine [18,19,20], trazodone [5], acetaminophen [3,6], salicylates [3] and malathion [21]. 2.…”
Section: Introductionmentioning
confidence: 99%
“…the toxicologist's point of view). According to the literature, drugs already detected in larvae include barbiturates (phenobarbital [1], secobarbital [2], amylobarbital and barbital [3]), benzodiazepines (diazepam [4], temazepam [5]), antidepressants (amitriptyline [5,6,7,8,9], nortriptyline [7], trimipramine [5]), opiates/opioids (morphine+codeine [10,11,12,13,14,15,16], propoxyphene [6]), amphetamine derivatives (amphetamine [3], MDMA +MDA [17]), cocaine and/or benzoylecgonine [18,19,20], trazodone [5], acetaminophen [3,6], salicylates [3] and malathion [21]. 2.…”
Section: Introductionmentioning
confidence: 99%
“…[25] and Benecke [26]. Both in the sunlit carcasses and in the shaded one the mouth and the wound were the preferred places for the setting.…”
Section: Oviposition Patternsmentioning
confidence: 99%
“…Goff et al studied the effects of cocaine (Goff et al 1989) and heroin ) on the rate of development in Sarcophagidae and demonstrated that maggots of Boetterisca peregrina develop more rapidly if reared on the liver or spleen of rabbits which had been killed by a lethal dose of cocaine or heroin. This illustrates the potential impact of drugs when estimating postmortem intervals by calculating the rate of development.…”
Section: Entomotoxicologymentioning
confidence: 99%
“…Bourel et al (1999) showed that an underestimation of the postmortem interval up to 24 h is possible if the presence of morphine in tissue is not considered when calculating the development time of Lucilia sericata. In a suicide case where the pesticide malathion had been used, the development stages of two blowflies, Chrysomya megacephala and C. rufifacies, found on the dead body, indicated a minimum postmortem interval of 5 days, although the victim had last been seen alive 8 days prior to the discovery of his body (Gunatilake and Goff 1989). The authors concluded that malathion in the tissues delayed the colonization by insects for several days.…”
Section: Entomotoxicologymentioning
confidence: 99%